Beginning Rails 3 : a beginner's guide to building web applications with Ruby on Rails - Carneiro, Cloves (Expert's voice in Web development., 2010)
"Beginning Rails 3 is the practical starting point for anyone wanting to learn how to build dynamic web applications using the latest release of the Rails framework for Ruby. You'll learn how all of the components of Rails fit together and how you can leverage them to create sophisticated web applications with less code and more joy. This book is particularly well suited to those with little or no experience with web application development, or who have some experience but are new to Rails. Beginning Rails 3 assumes basic familiarity with web terms and technologies, but doesn't require you to be an expert. Rather than delving into the arcane details of Rails, the focus is on the aspects of the framework that will become your pick, shovel, and axe. Part history lesson, part introduction to object-oriented programming, and part dissertation on open source software, this title doesn't just explain how to do something in Rails, it explains why"--Resource description page.